Exercise‐induced histone H3 trimethylation at lysine 27 facilitates the adaptation of skeletal muscle to exercise in mice. (12th June 2022) - Shimizu, Junya; Kawano, Fuminori
Abstract : Abstract: Histone H3 trimethylation at lysine 27 (H3K27me3) is known to act as a transcriptionally repressive histone modification via heterochromatin formation. In skeletal muscle, it was also reported that H3K27me3 was enriched at the sites transcriptionally activated by exercise, although the role of H3K27me3 in adaptation to exercise is unknown. In this study, using mouse tibialis anterior muscle, we initially determined the genome‐wide enrichment of RNA polymerase II and histone H3 trimethylation at lysine 4 (H3K4me3) and H3K27me3 using chromatin immunoprecipitation, followed by sequencing analysis. The loci that were transcriptionally upregulated by a single bout of running exercise were marked by both H3K27me3 and H3K4me3, which were also correlated with the distribution of RNA polymerase II. The genes that were not responsive to exercise exhibited high H3K4me3 occupancy, similar to the upregulated genes but with less H3K27me3. Next, we tested the effects of GSK343, a specific inhibitor of enhancer of zeste homologue 2 (EZH2). Unexpectedly, GSK343 administration enhanced the H3K27me3 occupancy at the target loci, leading to the upregulation of gene responses to acute exercise. Administration of GSK343 also facilitated the phenotypic transformation of type IIb to type IIa fibres and the upregulation of AMPK phosphorylation and levels of heat shock protein 70, pyruvate dehydrogenase kinase 4, peroxisome proliferator‐activated receptor γ coactivator‐1α and muscle RING finger 1. Furthermore, in contrast to the accelerated adaptation to exercise by GSK343, administration of the EZH1/2 dual inhibitor valemetostat prevented the changes in the aforementioned parameters after exercise training. These results indicate that exercise‐induced H3K27me3 plays a key role in inducing exercise‐related effects in the skeletal muscle. Key points: Exercise mediates histone H3 trimethylation at lysine 27 (H3K27me3) at transcriptionally upregulated loci in skeletal muscle, but the role of H3K27me3 in the adaptation of skeletal muscle to exercise training is unclear. Chromatin immunoprecipitation followed by sequencing analysis demonstrated that H3K27me3, in addition to H3K4me3 modifications, is the hallmark of sites showing higher responses to acute exercise. GSK343, a selective inhibitor of the enhancer of zeste homologue 2 (EZH2), enhanced the gene responses to a single bout of exercise and accelerated the adaptive changes during exercise training in association with myonuclear H3K27me3 accumulation. Administration of valemetostat, an EZH1/2 dual inhibitor, repressed myonuclear H3K27me3 accumulation during training and caused a failure of adaptive changes. Exercise‐induced H3K27me3 might play a key role in inducing exercise‐related effects in skeletal muscle. Abstract : Abstract figure legend The loci upregulated in response to exercise in mouse skeletal muscle are characterized by a bivalent modification with histone H3 trimethylation at lysine 27 (H3K27me3) and lysine 4 (H3K4me3). Acute exercise further stimulates both H3K27me3 and H3K4me3 at these loci associated with the upregulation of gene transcription. Administration of the lysine methyltransferase EZH2‐specific inhibitor GSK343 increased H3K27me3 and H3K4me3 occupancies at the target loci after a single bout of exercise. Chronic treatment with GSK343 during exercise training upregulated H3K27me3 further in muscle fibres. In addition, it increased the number of muscle fibres expressing type IIa myosin heavy chain (MyHC) and enhanced the adaptive changes in the related protein levels. In contrast, administration of valemetostat, an EZH1/2 dual inhibitor, decreased H3K27me3 and H3K4me3 occupancies after acute exercise and caused a failure of the exercise‐induced effects after training. It was also suggested that EZH1 acted as a modifier of exercise‐induced H3K27me3 in skeletal muscle.